ISSUES OF EDUCATIONAL MOTIVATION AND WAYS TO SOLVE THEM - PETROVA, OLGA V.; KUZNETSOVA, VALENTINA A. (Челябинский гуманитарий, 2025)
The article describes the problems of students’ motivation towards high-quality knowledge, universal learning activities, functional literacy; presents facts confirming parents’ and teachers’ concerns about low educational motivation; outlines a plan developed by the teaching staff aimed at addressing this issue. Additionally, it clarifies the working definition of educational motivation based on materials from Peterson L. G., Anisimova O. S., and Agapov Y. V. It provides justification for specific tasks that have been solved or are yet to be addressed by the pedagogical team of MAOU “School No. 104 of Chelyabinsk.” The connection between setting goals and objectives with previous work as part of a Regional Innovative Platform and Federal Innovative Platform related to formative criterion-based assessment and activity-based learning technology of the Center for System-Activity Pedagogy “School 2000...” is demonstrated. The article also identifies challenges, reasons for difficulties faced by teachers in fostering motivation, and highlights demotivators. Arguments supporting the necessity of creating success situations for each individual student are presented, drawing upon speeches byV. A. Sukhomlinsky and N. E. Shurkova. Practical tips for teachers in the form of tables are provided for selecting topics and methodological products adapted to specific directions of motivational development. Initial results of project implementation are described.